The Influence of Competence and Autocratic Leadership Style on the Performance of Employees at Cileungsi Regional General Hospital Through Work Discipline as a Mediating Variable - Lukman Darmawan; Titing Widyastuti (Pustaka Digital Indonesia, 2025)
This study aims to analyze the influence of competence and autocratic leadership style on the performance of employees at Cileungsi Regional Hospital, with work discipline as a mediating variable. The statistical test results indicate that both competence and autocratic leadership style significantly affect employees' work discipline and performance. Work discipline also serves as a mediating variable that strengthens the relationship between competence and autocratic leadership style with employee performance. These findings highlight the importance of continuous competency development through training and the implementation of a firm yet adaptive leadership style suited to employee characteristics. Hospital management is advised to enhance monitoring systems, conduct regular performance evaluations, and enforce fair and consistent work discipline to create a productive and high-quality work environment.